Ideology - Plamenatz, John (London, 1970)
It was when philosophers considered the social conditions within which men acquire ideas and construct theories, and when they noticed how greatly ideas vary from one society to another and how they change through time that the concept of ideology for rather the cluster of concepts arose in its widest meaning an ideology is the entire range of ideas present in a society or epoch. But the word is also and more frequently used in narrower senses to refer only to some kinds of ideas or beliefs, or to ideas and beliefs peculiar to one social group Again, ideologies are often said to be sorialls conditioned and to have some social function, but those who speak in this way have different sometimes obscure, ideas about conditioning and functions. This book attempis to introduce order into a tangled area of social theors be discussing ideology in a broad philosophical manner, explaining the importam uses of the term, their differences and relationships and how each has gained currency. The book devotes considerable attention what Mary said abour ideology not because it is abour Marxisin bot because Mars introduced the concept into social studies in a major was To contrast his formulations of problems with those of other thanker is often of the best way of explaining how confused our ideas about ideology are and how this prevents out amiculang problems relating to ideologs in a way that they can be salved. This book however, does not set forth to su problems, a instead contributes to the clearer, systemas exprevod problems.
Keywords: Ideology